Dalle Baccanti all’Ibiza-Gate. «Schwarzwasser» di Elfriede Jelinek: [From the Bacchae to the Ibiza-Gate. Elfriede Jelinek’s «Schwarzwasser»] (Studia austriaca, 2022)
Taking studies on deconstruction, performance theories, and pragmatics as my point of departure, I investigate Elfriede Jelinek’s last political play Schwarzwasser (2020), where the so-called Ibiza-gate – which in 2018 involved the former Vice Chancellor of Austria – is represented. In her interpretation, Jelinek refers to René Girard’s Violence and the Sacred and Euripides’ Bacchae in an intertextual dialogue. This contribution aims to show how and why Jelinek recalls and employs The Bacchae in her play and to establish a connection between the political function of Greek theatre and Jelinek’s view of Austrian populism.